Emergency physician perspectives on initiating buprenorphine/naloxone in the emergency department: A qualitative study. Issue 2 (29th April 2021) - Dong, Kathryn A.; Lavergne, Karine J.; Salvalaggio, Ginetta; Weber, Savannah M.; Xue, Cindy Jiaxin; Kestler, Andrew; Kaczorowski, Janusz; Orkin, Aaron M.; Pugh, Arlanna; Hyshka, Elaine
Abstract: Objectives: The objective of this study was to examine the perspectives of Canadian emergency physicians on the care of patients with opioid use disorders in the emergency department (ED), in particular the real‐world facilitators to prescribing buprenorphine/naloxone (BUP) in the ED. Methods: We conducted semistructured qualitative interviews using a multi‐site–focused ethnographic design. Purposive sampling via an existing national research network was used to recruit ED physicians. Interviews were conducted by phone using an interview guide and continued until theoretical data saturation was reached. Interviews were transcribed and analyzed using latent content analysis. Interviews took place between June 21, 2019, and February 11, 2020. Results: A total of 32 physicians were included in the analysis. Participants had a median of 10 years of experience, and most (29/32) worked in urban settings. Clinical care of patients with opioid use disorder was found to be variable and physician dependent. Although some physicians reported routinely prescribing BUP, others felt that this was outside the clinical scope of emergency medicine. Access to clinical pathways, incentivized training, dedicated human resources, and follow‐up care were identified as critical facilitators for supporting BUP prescribing. Participants also identified a shared responsibility between patients and the ED, including the importance of a patient‐centered approach that enhanced patient autonomy. ED BUP prescribing became self‐reinforcing over time. Conclusions: Although there remains practice variability among Canadian emergency physicians, successful implementation of ED BUP prescribing has occurred in some locations. Jurisdictions wanting to facilitate BUP uptake should consider providing incentivized training, treatment protocols, dedicated human resources, and streamlined access to follow‐up care.